Vocalism in the Continental runic inscriptions - Findell, Martin (2010)
The goal of this thesis is the phonological analysis of a corpus of runic inscriptions in order to reconstruct the vocalic system(s) of the West Germanic dialects spoken in the Continental interior between the 5th-7th centuries A.D. The thesis presents a brief outline of the late Proto-Germanic vocalic system and of the principal sound changes involved in the development of the later dialects of the region (Old High German and Old Saxon). The main part of the thesis surveys the data retrievable from the runic inscriptions in an attempt to determine to what extent (if any) these sound changes are in evidence. In many respects, the data are consistent with the anticipated developments attested in OHG and OS; but for some of the sound changes – particularly those affecting the diphthongs – the existing models do not satisfactorily account for the data. There is also some evidence for processes not normally identified in accounts of the phonological background of the later dialects.